2021
DOI: 10.21203/rs.3.rs-371532/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distance Visual Acuity Versus Near Visual Acuity in Amblyopia.

Abstract: Purpose: To measure and compare distance and near visual acuity in amblyopic patients.Methods: This study was evaluated 167 patients with amblyopia between ages of 6 and 55 years. In all subjects, a comprehensive ophthalmic examination including visual acuity, refraction, slit lamp biomicroscopy, and funduscopy was performed. Distance visual acuity (DVA) was measured by Snellen chart at 4 m and near visual acuity (NVA) was measured by Snellen chart at 40 cm, and then DVA and NVA were compered and analyzed.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A recent study showed that near visual acuity was better than distance visual acuity in amblyopic patients, so that near visual acuity tests can be used to increase the sensitivity and specificity of the distance visual acuity tests for screening and diagnosis of amblyopia. However, other studies do not find this difference and think it is likely due to test-retest variability [ 35 , 36 ]. This is also an aspect we have to take into account.…”
Section: Discussionmentioning
confidence: 86%
“…A recent study showed that near visual acuity was better than distance visual acuity in amblyopic patients, so that near visual acuity tests can be used to increase the sensitivity and specificity of the distance visual acuity tests for screening and diagnosis of amblyopia. However, other studies do not find this difference and think it is likely due to test-retest variability [ 35 , 36 ]. This is also an aspect we have to take into account.…”
Section: Discussionmentioning
confidence: 86%
“…Limitations are that near acuity (OKKO-app) may overestimate "true" distance acuity, though evidence is conflicting. 2,3 Comparing the vanishing-optotype, picture-only OKKO-TAO-prototype with a non-vanishing optotype picture/letter reference standard may also have affected the accuracy of our comparison.OKKO-Health is the first application specifically designed for home acuity-testing in young children by parents/carers, using TAO optotypes. Previous studies used orthoptistsupervised remote testing 4 or letter optotypes, 5,6 some requiring both a computer display and a handheld device, increasing complexity for the user.…”
mentioning
confidence: 99%
“…Limitations are that near acuity (OKKO-app) may over-estimate “true” distance acuity, though evidence is conflicting. 2,3 Comparing the vanishing-optotype, picture-only OKKO-TAO-prototype with a non-vanishing optotype picture/letter reference standard may also have affected the accuracy of our comparison.…”
mentioning
confidence: 99%